Podcasts and English vocabulary, among first-year high school students, at a public institution in Loja, during the 2022-2023 school year. - Palacios Feijoo, Emily Jhuliana (2023)
Vocabulary is an important component in learning and teaching of a foreign language, laying the groundwork for effective communication. This research aimed to investigate the impact of podcasts use on English vocabulary improvement among first-year high school students in a public institution in Loja during the 2022-2023 school year. To meet the proposed objective, this study included 18 first-year high school students in a public institution in Loja, Ecuador. The study used an action research design with a mixed approach, collecting quantitative data and qualitative data obtained through a pretest, posttest, questionnaire and field notes. The data collected and analyzed were presented using descriptive statistics and thematic analysis. In this study, the quantitative analysis revealed a significant increase in students' English vocabulary, with an average on the posttest (6.44) differing markedly from the average on the pretest (4.05 points). Mixed data from field notes and questionnaires highlighted positive student experiences, active participation, and motivation when podcast-based activities were integrated. Although this research showed encouraging results, it is so essential to recognize the limitations and possible challenges faced during the study. In conclusion, the study emphasizes the importance of vocabulary in language learning and teaching, as well as the positive impact of using podcasts to improve students' English vocabulary competency. Keywords: teaching-learning, foreign language, vocabulary improvement, podcast